Sustainable water supply: Potential of recycling laundry wastewater for domestic use - Omolara Lade; Zainab Gbagba (Journal of Civil Engineering and Environmental Sciences - Peertechz Publications, 2018)
To reduce the consumption of freshwater in the laundry industry, a new trend of separating waste water has resulted in the reuse/recycling of water. In this study, the characteristics of domestic laundry wastewater was evaluated using wastewater samples from four selected laundries. The samples were analysed for the physicochemical and bacteriological characteristics of the water. The parameters examined were: pH, temperature, conductivity, TDS, TSS, turbidity, colour, total hardness, BOD, COD, DO, phosphate, nitrate, chloride and sulphate. The pH of the wastewater ranges from 8.8 - 9.0, TDS ranges from 229 mg/L to 461mg/L, TSS ranges from 228.9-460 mg/L, Turbidity ranges from 25.3- 39.4 NTU and the colour ranges from 4.2-5.8 TCU. The BOD ranges from 144- 211.2 mg/L and the COD ranges from 428.6-531.3 mg/L. The Total Coliform and E.coli in the wastewater ranges from 140-700 CFU. The pH, TDS, colour, total hardness, total coliform and E.coli are within permissible level for toilet and laundry water reuse while TSS, turbidity, BOD and COD exceeds the limit. The result of this study reveals that there is a high potential of recycling laundry waste water for reuse in toilet, irrigation and laundry with little treatment.